2003
DOI: 10.5650/jos.52.159
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Triacyiglycerol by Laccase-Natural Mediator and Laccase-Mediator Derived from Natural Compound Systems.

Abstract: Laccase, a type of polyphenoloxidase, was found to oxidize unsaturated triacylglycerol under mild reaction conditions in the presence of a simple natural mediator and mediator which is derived from a natural compound. The oxidized products were characterized by UV-and IR-spectroscopic analyses, ferric thiocyanate peroxide analysis and size exclusion chromatography. It was considered that conjugated diene peroxide units were formed in the triacylglycerol without substantial polymerization or degradation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…However, as laccase is an oxidoreductase, previous experimental reports have shown that laccase reduces the oxidative stability of lipids by oxidation of phenols and PUFA, resulting in the oxidative loss of lipids and PUFA. [ 25,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, as laccase is an oxidoreductase, previous experimental reports have shown that laccase reduces the oxidative stability of lipids by oxidation of phenols and PUFA, resulting in the oxidative loss of lipids and PUFA. [ 25,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Johannes and Majcherczyk succeeded in the degradation of polycyclic aromatic hydrocarbons by the laccase/mediator system using natural mediators (22). Saba and Nakano also reported that HBA and HBA derivatives were effective in oxidizing triacylglycerol as natural mediators (23). We investigated the degradation of dymron by the laccase/mediator system using natural mediators ( Figure 10).…”
Section: Screening Of Enzymes Capable Of Dymron Degradationmentioning
confidence: 99%
“…The oxidation of unsaturated fatty acids and triglycerols by the laccase-mediator systems has already been investigated by different working groups. [24][25][26][27][28] The best results were achieved with 1-hydroxybenzotriazole (HBT) and 2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) as mediators.…”
Section: Introductionmentioning
confidence: 99%